Recovery of decomposition rates and decomposer invertebrates during rain forest restoration on disused pasture. (5th July 2019) - Stone, Marisa J.; Shoo, Luke; Stork, Nigel E.; Sheldon, Fran; Catterall, Carla P.
Abstract: Converting forest to pasture can alter the roles of biota in ecosystem functioning, while vegetation restoration should arguably assist functional recovery. Since tests of this are scarce, this study quantifies both litter decomposition rates and their association with decomposer invertebrates, across 25 sites representing different phases of deforestation and subsequent reforestation of rain forest. Open and closed (to exclude macro‐invertebrates) mesh bags containing forest leaves were exposed in the field for up to eight months, and invertebrates were extracted from separate collections of ground surface litter. Sites spanned five vegetation categories (five sites in each): reference states of both old‐growth forest and grazed pasture; unassisted woody regrowth aged 20–50 years on former pasture; and assisted regeneration aged 1–3 and 5–10 years after interventions were applied to similar regrowth. Decomposition rates in open bags were about 50% slower in pasture than old‐growth forest, and abundances of macro‐ and meso‐decomposer invertebrates were 95% and 77% lower, respectively. However, in all restoration site‐types, decomposition rates had recovered to 83% of old‐growth values, and abundances of invertebrate decomposers were similar in old‐growth forest. Decomposer community composition at a broad taxonomic level differed strongly between pasture and all other vegetation types. Exclusion of macro‐invertebrates decreased decomposition rates by only about 3.1%, but decomposition rates in open bags were significantly correlated (across sites) with abundances of both macro‐ and meso‐decomposers, most strongly so for meso‐decomposers. Drawing useful generalizations across studies is impeded by differing methodologies and because few include both agricultural and forest reference sites.